Epidemiology of accidents in tile factories of Mangalore city in Karnataka - Kumar S; Rathnakar U; Harsha Kumar H (Wolters Kluwer Medknow Publications, 2010)
Background: Occupational accidents are a major point of concern in industries. The academic community should take the first step to address the long-neglected concerns of occupational safety. Objective: To assess the prevalence and pattern of occupational accidents. Materials and Methods: A record-based, cross-sectional study was done in three tile factories of Mangalore city, in Karnataka. A total of 416 workers were analyzed for the year 2004, and data regarding age, sex, job duration, type and nature of injury, body parts involved, and time of injury were collected in a prestructured proforma. Statistical Analysis: Proportions, Chi- square test, Univariate and Multivariate analysis. Results: The overall prevalence rate of accidents was found to be 18.5%. It was found that almost around 86% of the accidents had affected the limbs (upper limb 24.7%, lower limb 61%), around half (52%) of the injuries were contributed by superficial injuries, 40% of accidents were due to stepping/striking against objects and while handling. Hand tools and machinery in motion contributed to around 20% of the accidents. Accidents were more common among the younger age group and less-experienced workers. Multiple logistic regression analyses revealed that the age group of 30-39 years had an independent significant association with accidents (OR = 0.21, P = 0.04). Conclusion: Accidents in tile industries are an important occupational health problem in this area of the country. There is a need for proper safety training of the workers.